Readability of the Translation of Figure of Speech in Srimad Bhagavatam From English Into Indonesian - Dewi Yulianti, Ni Ketut; Pastika, I Wayan; Artawa, Ketut; Putra Yadnya, Ida Bagus (e-Journal of Linguistics, 2017)
The research is a descriptive translation study focusing on the methods and ideology of translation of figure of speech used in the text of Srimad Bhagavatam into Indonesian. It departed from a translation paradigm that considered Srimad Bhagavatam as a product, and the impact of the methods and ideology applied to the readability level of figure of speech translation contained in Srimad Bhagavatam from English to Indonesian. This is a library study and the method used in collecting the data is observation, by reading the studied text carefully on the sentences that contain figure of speech. Data collection technique used is a qualitative one, namely by determining and explaining the methods and ideology embraced by the translator in translating the figure of speech. To view the translation readability level, three informants are involved to complete a questionnaire containing about the readability level of translation. This study shows that the ideology held by the translator is domestication by applying a communicative method of translation on most sentences with figure of speech. Overall, all translation methods used by the translator has a positive impact on the readability level of figure of speech translation from English into Indonesian.
Keywords: readability, figure of speech, translation, Srimad Bhagavatam